Antimicrobial Photodynamic Inactivation Inhibits Candida albicans Virulence Factors and Reduces In Vivo Pathogenicity - Kato, Ilka Tiemy (American Society for Microbiology, 2013)
The objective of this study was to evaluate whether Candida albicans exhibits altered pathogenicity characteristics following sublethal antimicrobial photodynamic inactivation (APDI) and if such alterations are maintained in the daughter cells. C. albicans was exposed to sublethal APDI by using methylene blue (MB) as a photosensitizer (0.05 mM) combined with a GaAlAs diode laser (λ 660 nm, 75 mW/cm(2), 9 to 27 J/cm(2)). In vitro, we evaluated APDI effects on C. albicans growth, germ tube formation, sensitivity to oxidative and osmotic stress, cell wall integrity, and fluconazole susceptibility. In vivo, we evaluated C. albicans pathogenicity with a mouse model of systemic infection. Animal survival was evaluated daily. Sublethal MB-mediated APDI reduced the growth rate and the ability of C. albicans to form germ tubes compared to untreated cells (P < 0.05). Survival of mice systemically infected with C. albicans pretreated with APDI was significantly increased compared to mice infected with untreated yeast (P < 0.05). APDI increased C. albicans sensitivity to sodium dodecyl sulfate, caffeine, and hydrogen peroxide. The MIC for fluconazole for C. albicans was also reduced following sublethal MB-mediated APDI. However, none of those pathogenic parameters was altered in daughter cells of C. albicans submitted to APDI. These data suggest that APDI may inhibit virulence factors and reduce in vivo pathogenicity of C. albicans. The absence of alterations in daughter cells indicates that APDI effects are transitory. The MIC reduction for fluconazole following APDI suggests that this antifungal could be combined with APDI to treat C. albicans infections.